2021
DOI: 10.1093/ecco-jcc/jjab076.525
|View full text |Cite
|
Sign up to set email alerts
|

P401 Risk of severe COVID-19 outcomes associated with inflammatory bowel disease medications: Reassuring insights from the United Kingdom PREPARE-IBD multicentre cohort study

Abstract: Background During the early COVID-19 pandemic, the British Society of Gastroenterology (BSG) developed a risk stratification grid to inform the United Kingdom (UK) government regarding strict social isolation, termed “shielding”. This advised inflammatory bowel disease (IBD) patients thought to be most clinically vulnerable to SARS-CoV-2 infection or severe COVID-19 outcomes, to stay at home and minimize face to face contact, even with household members. Those considered at highest risk inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…From the initial 811 studies identified in the search, 18 studies 17–33 met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the initial 811 studies identified in the search, 18 studies 17–33 met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Search results. From the initial 811 studies identified in the search, 18 studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data used in evaluating the association between adverse outcomes and IBD drugs were obtained from the 12 included studies and the SECURE-IBD registry, including 1474 adverse and 7445 mild cases [ 23 , 33 , 41 , 42 , 44 47 , 50 – 52 ]. The pooled OR of mesalazine (1.79; 95% CI 1.59–2.02; I 2 = 44%; P = 0.05), corticosteroids (1.66; 95% CI 0.99–2.78; I 2 = 64%; P < 0.01), IMS (1.30; 95% CI 1.10–1.53; I 2 = 45%; P = 0.04), anti-TNF (0.47; 95% CI 0.41–0.53; I 2 = 0%; P = 0.59) are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 However, data from the SECURE-IBD registry, including 525 patients internationally with IBD and COVID-19 infection, and analyses of 600 patients with rheumatic disease from the Global Rheumatology Alliance registry, suggest that systemic corticosteroids increase the risk of severe COVID. [19][20][21] Our primary finding that 3-month steroidfree outcomes were comparable pre-and mid-pandemic despite the shift towards poorly bioavailable steroid flare induction treatment is therefore important and reassuring. Biologics can then be safely instituted, notwithstanding the potential effect on vaccine efficacy, which may influence the timing of biologic commencement, as we move towards consideration of long-term disease management in the context of COVID-19 risk.…”
Section: F I G U R E 5 Clinical Outcomes In Thementioning
confidence: 93%